2018
DOI: 10.3389/fphys.2017.01098
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Three-Dimensional (3D) Assessment Method for Clubfoot—A Study Protocol

Abstract: Background: Congenital talipes equinovarus (CTEV) or clubfoot is a common pediatric congenital foot deformity that occurs 1 in 1,000 live births. Clubfoot is characterized by four types of foot deformities: hindfoot equinus; midfoot cavus; forefoot adductus; and hindfoot varus. A structured assessment method for clubfoot is essential for quantifying the initial severity of clubfoot deformity and recording the progress of clubfoot intervention.Aim: This study aims to develop a three-dimensional (3D) assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Burhan et al reported that the Kinect® XBOX 360 gaming sensor is capable of producing 3D reconstructed geometry in designing orthotic with good functionality [25]. Only one study investigated changes in clubfoot structure and thermo-physiological functioning status during each casting step of clubfoot treatments using a Kinect 3D scanner and an infrared camera [26]. The purpose of this study is to employ a Kinect 3D scanner to do a threedimensional assessment of clubfoot in order to establish the severity of the problem at the outset and to track structural changes in the clubfoot after each casting intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Burhan et al reported that the Kinect® XBOX 360 gaming sensor is capable of producing 3D reconstructed geometry in designing orthotic with good functionality [25]. Only one study investigated changes in clubfoot structure and thermo-physiological functioning status during each casting step of clubfoot treatments using a Kinect 3D scanner and an infrared camera [26]. The purpose of this study is to employ a Kinect 3D scanner to do a threedimensional assessment of clubfoot in order to establish the severity of the problem at the outset and to track structural changes in the clubfoot after each casting intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Clubfoot, also known as Congenital Talipes Equinovarus, represents a frequent pediatric congenital deformity of the foot, occurring 1 in 1.000 live births. [ 1 ]…”
Section: Introductionmentioning
confidence: 99%